Capacity increasing of a cellular network using multibeam antenna - Hoque, Ifthakharul (BRAC University, 2016)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2016.